Norsk Kan Hjelpe! A Study of Student Perceptions, Abilities, and Confidence in the Teaching of Intercomprehension of the Romance Languages and How the Use of a Norwegian Text Unlocks Students' Potential - Oliva, Cedric Joseph (Nouvelle Revue Synergies Canada, 2025)
In North America, over 70 million people know English and a Romance Language (often Spanish). Many students who enter college or university already possess such bilingual or plurilingual skills. The Intercomprehension of the Romance Languages: a Pathway to Plurilingualism courses (California State University, Long Beach (2014–2026), St. Lawrence University (2018), Bryant University (2023–2026)) offer a manner to foster linguistic growth for such students. The article expands on previous research (Oliva & Gómez Larriva, 2020) on students’ linguistic PCA (predispositions, confidence, and ability) scores that studies their perception when they mobilize their linguistic repertoire and approach unknown languages (Tyvaert, 2008) through proximity strategies, as “[n]o foreign language is totally unknown territory” (McCann et al., 2003, p. 8). It then explores the value of studying texts in Germanic languages to help heighten student confidence when reading unknown texts in Romance languages by revealing the applicability of intercomprehensive strategies beyond the scope of Romance languages.